2013
DOI: 10.1016/j.cryobiol.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose and glycerol have a dose-dependent synergistic effect on the post-thawing quality of ram semen cryopreserved in a soybean lecithin-based extender

Abstract: The objective of this study was to examine the interaction of different concentrations of trehalose [0 (T0), 50 (T50) or 100 (T100) mM] and glycerol [5% (G5) or 7% (G7)] on post-thawed quality of ram semen, cryopreserved in a soybean lecithin (SL)-based extender. Twenty-eight ejaculates were collected from four rams and diluted with six trehalose/glycerol combinations: T0G5, T50G5, T100G5, T0G7, T50G7, and T100G7. Sperm motility (CASA), membrane integrity (eosin/nigrosin) and functionality (HOST), abnormal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 51 publications
3
37
0
2
Order By: Relevance
“…(2009) found that supplementation of semen extender with 50 and 100 mM concentrations of trehalose improved the post thawing results of ram spermatozoa, and 100 trehalose exerted more cryoprotective effect on sperm characteristics compared to the other and control groups significantly (p<0.05). Najafi et al (2013) reported that Trehalose 100mM with 5% glycerol significantly reduced membrane damage in sperm cells after thawing, while 100mM trehalose with 7% glycerol did not produce better results. In ram (Jafaroghliet al 2011), goat (Khaliliet al 2009) and buffalo, membrane integrity was better preserved when trehalose was used at 100 mM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) found that supplementation of semen extender with 50 and 100 mM concentrations of trehalose improved the post thawing results of ram spermatozoa, and 100 trehalose exerted more cryoprotective effect on sperm characteristics compared to the other and control groups significantly (p<0.05). Najafi et al (2013) reported that Trehalose 100mM with 5% glycerol significantly reduced membrane damage in sperm cells after thawing, while 100mM trehalose with 7% glycerol did not produce better results. In ram (Jafaroghliet al 2011), goat (Khaliliet al 2009) and buffalo, membrane integrity was better preserved when trehalose was used at 100 mM.…”
Section: Resultsmentioning
confidence: 99%
“…The present study was carried out at ICAR-National Dairy Research Institute (NDRI), Eastern Regional Station, Kalyani, West Bengal, India.A total of 24 semen ejaculates were collected from adult Black Bengal bucksusing artificial vagina.The basic extender was prepared by mixing 300 mMTris, 28 mM glucose, 95 mM citric acid, soybean lecithin 1% (w/v), 5% glycerol (v/v), and gentamicin 500 µg/ml in distilled water.Trehalose was added @ 0 (T0-control), 50mM (T50), 100mM (T100) and 150mM (T150) to the extender (Najafi et al 2013).Each ejaculate wassplit into four equal aliquots and diluted at 37°C for extension in extenders containing different concentrations of trehalose. Filling and sealing of straws was done manually at room temperature (25°C to 27°C) in 0.25 ml French mini straws.…”
Section: Methodsmentioning
confidence: 99%
“…Lyophilized or fresh egg yolk Similar cryoprotective effects Alcay et al, 2015 Natural or lyophilized low density lipoproteins Total and progressive motility Moustacas et al, 2011 Casein, palm oil, coconut oil or egg yolk Egg yolk is superior Del Valle et al, 2013 Different species' egg yolk Sperm quality by 15% chucker egg yolk Kulaksiz et al, 2010 -Egg yolk concentration -Bioexcell ® or egg yolk -Optimal concentration: 5-10% -Bioexcell ® may be an alternative Gil et al, 2003 Soybean concentrations between 1-1.5% Motility, viability, membrane integrity - Emamverdi et al, 2013-Forouzanfar et al, 2010 Soybean lecithin or egg yolk 1% soybean lecithin similar with 20% egg yolk extenders Masoudi et al, 2016 Soybean lecithin concentration -Soy lecithin > 1% : semen quality -Soy lecithin > 3.5% : no significant effect on motility -Soy lecithin 3.5% : mitochondrial activity One-step or at 5° C two-steps glycerol addition No effect on motility and viability Morrier et al, 2002 4% glycerol in a two-step dilution (to 2% at 35 o C and to 4% at 5 o C) Good field fertility rate Anel et al, 2003 Osmolality of glycerol based extenders in a two-step dilution High osmotic pressure (400 mOsm) Soylu et al, 2007 Glycerol alone or in combination with trehalose 5% glycerol and 100 mM trehalose: post-thawing sperm quality Najafi et al, 2013 -100 mM trehalose with 5% glycerol -100 mM trehalose and 8% LDL High post-thawing semen quality - Jafaroghli et al, 2011-Tonieto et al, 2010 Trehalose in combination with fructose Motility and viability Matsuoka et al, 2006 Trehalose, sucrose, raffinose, hypotaurine High ram semen cryo-protection - Bucak et al, 2013-Jafaroghli et al, 2011 Cyclodextrins pre-loaded with cholesterol Binding capacity to zona pellucida Mocé et al, 2010 Seminal plasma -Semen quality and fertility rate -No beneficial effect on sperm quality Uysal and Bucak (2007) observed that the addition of lycopene, a natural carotenoid which occurs in certain fruits and vegetables, in a Tris-based extender exhibited high protection of all tested ram semen parameters after thawing. Similar results were obtained by the supplementation of soybean lecithin extender with 4 or 6% rosemary aqueous extract (Motlagh et al, 2014).…”
Section: Results Publicationsmentioning
confidence: 99%
“…Najafi et al (2013) demonstrated that in a soybean lecithin-based extender, the combination of 5% glycerol and 100 mM trehalose resulted in higher post-thawing sperm quality (motility, viability, morphology, acrosome and plasma membrane integrity) than other combinations, or using glycerol alone, indicating a synergistic effect. These findings agree with Jafaroghli et al (2011), who obtained the highest post-thawing semen quality by the combination of 5% glycerol with 100 mM trehalose in a Tris-citric acid-fructoseyolk extender.…”
Section: ) Research Concerning "Sugars" Effects and Propertiesmentioning
confidence: 99%
“…Semen cryopreservation may lead to oxidative, chemical and physical damages on sperm membrane leading to reduction of sperm viability and fertility (Evans et al, 1987;Watson, 2000;Emamverdi et al, 2014;Najafi et al, 2014a;Sarıözkan et al, 2015). Freezing process mostly leads to loss of motility, acrosomal and plasma membrane functionality of spermatozoa (Tuncer et al, 2011;Najafi et al, 2013;Shahverdi et al, 2015). Moreover, because of high amount of polyunsaturated fatty acids in mammalian spermatozoa (plasma membrane), bull spermatozoa is very susceptible to oxidative stress which can influence on the quality and fertility potential of spermatozoa (Zanganeh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%